Green Accounting to Supporting Sustainable Development Goals of Tourism Objects in Bandar Lampung - Putri, Rosydalina (Institut Bisnis dan Informatika Kesatuan, 2024)
Government Regulation of the Republic of Indonesia Number 46 of 2017 requires all business sectors to implement environmental instruments in their economic activities. This is in line with the global action formed by the UN in 2015 to be able to realize the sustainability development goals in 2030. The tourism sector is one of the places that can educate the public in environmental conservation. This study aims to analyze the implementation of green accounting and identify the extent of the role of green accounting in supporting the sustainability development goals at tourist attractions in Bandar Lampung. The design of this study is qualitative with documents, observations and interviews in data collection. The sample of this study amounted to 11 tourist attractions in Bandar Lampung that have made financial records according to PSAK no. 1 and applied the principles of green accounting in their financial records. The findings in this study state that the implementation of green accounting in tourist parks in Bandar Lampung has been implemented well and in accordance with the provisions for recording costs in green accounting. However, in the implementation there are still several indicators that have not been met. With the implementation of the green accounting concept in its financial records, tourist attractions in Bandar Lampung have an important role in supporting the SDGs goals that have been set by the world.